2004
DOI: 10.1136/jcp.2004.020552
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HPV infection and tumour markers in cervical intraepithelial neoplasia from cone biopsies of Mozambican women

Abstract: Aims: To evaluate human papillomavirus (HPV) infection in whole cervical cone specimens with cervical intraepithelial neoplasia (CIN). In addition, to evaluate the relation between the presence of CIN lesions and HPV infection and the expression of Ki-67, p53, cytokeratins, Gp230 glycoprotein, and simple mucintype carbohydrates. Methods: Cervical cone specimens from five patients with CIN were studied. For each specimen, serial sections encompassing the whole cone were collected (52 samples). HPV infection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…10 Our findings among cervical cancer cases are consistent with other smaller studies in Mozambique that also found that HPVs 16 and 18 were the most common types in tumor samples from these patients. [11][12][13][14] The results of these studies are consistent with the world-wide distribution of HPV types in cervical cancer. 7,15 Despite of the fact that HPVs 51 and 35 are the most frequently detected types in women without cervical abnormalities, HPV Types 16 and 18 are still the most frequently identified genotypes in cervical cancer specimens.…”
Section: Discussionsupporting
confidence: 83%
“…10 Our findings among cervical cancer cases are consistent with other smaller studies in Mozambique that also found that HPVs 16 and 18 were the most common types in tumor samples from these patients. [11][12][13][14] The results of these studies are consistent with the world-wide distribution of HPV types in cervical cancer. 7,15 Despite of the fact that HPVs 51 and 35 are the most frequently detected types in women without cervical abnormalities, HPV Types 16 and 18 are still the most frequently identified genotypes in cervical cancer specimens.…”
Section: Discussionsupporting
confidence: 83%
“…In other Sub-Saharan countries, the frequency of HPV16 and 18 varies. Some countries have reported patterns that resemble the situation in Europe and the United States [ 22 , 48 , 66 , 67 ], whereas in other countries, HPV types other than 16 and 18 appear to be more prominent [ 29 , 47 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increase in the awareness of the disease and improvements in the diagnostic capacity may have also played a role. Indeed, HPV infection, the cause of cancer of the uterine cervix has been shown to be highly prevalent in Mozambique with over 50% of the women being positive at 20 years of age and 20–30% of those over 30 years of age [ 20 22 ]. As in other low-income countries, the high prevalence of cancer of the uterine cervix may be explained by the difficulties in carrying out secondary prevention programs due to limited resources.…”
Section: Discussionmentioning
confidence: 99%